2017
DOI: 10.1016/j.addbeh.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between addictive use of social media, narcissism, and self-esteem: Findings from a large national survey

Abstract: Social media has become an increasingly popular leisure activity over the last decade.Although most people's social media use is non-problematic, a small number of users appear to engage in social media excessively and/or compulsively. The main objective of this study was to examine the associations between addictive use of social media, narcissism, and selfesteem. A cross-sectional convenient sample of 23,532 Norwegians (M age =35.8 years;range=16-88 years) completed an open web-based survey including the Ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

67
668
16
41

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 908 publications
(792 citation statements)
references
References 32 publications
67
668
16
41
Order By: Relevance
“…According to PBT, low self-esteem is among the personality risk factors that may lead to development of problem behaviors (Jessor 1991). Moreover, previous studies suggest that students with low self-esteem demonstrate more PSMU and CBP (Andreassen et al 2017;Fan et al 2016). Therefore, it is hypothesized that self-esteem will be negatively associated with CBP and PSMU.…”
Section: Self-esteem and Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to PBT, low self-esteem is among the personality risk factors that may lead to development of problem behaviors (Jessor 1991). Moreover, previous studies suggest that students with low self-esteem demonstrate more PSMU and CBP (Andreassen et al 2017;Fan et al 2016). Therefore, it is hypothesized that self-esteem will be negatively associated with CBP and PSMU.…”
Section: Self-esteem and Depressionmentioning
confidence: 99%
“…Furthermore, it has been suggested that depressive feelings and problematic behaviors may peak around the last years of high school (Bayram and Bilgel 2008;Hankin et al 2015). Based on previous studies (Andreassen et al 2017;Ševčíková and Šmahel 2009), it is hypothesized that younger emerging adults and older adolescent students will be more problematic social media users and cyberbullying perpetrators.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, not all online activities should be considered "causal" or "accidental" activities, since they can represent symbols or symptoms connected to the real identity. Moreover, several researchers have demonstrated the effect of narcissism on behaviours exhibited in the virtual world (Andreassen, Pallesen, & Griffiths, 2016;Lee & Sung, 2016). In addition, a positive correlation between poor mental health and frequent use of social networks during developmental age has been evidenced (Sampasa-Kanyinga & Lewis, 2015).…”
Section: Adolescents On Line Identity and Major Risky Online Behavioursmentioning
confidence: 99%
“…For example, SNS addiction has negative consequences for the individual as well as the society in which they reside ( [9]). For instance, research studies (e.g., [10] [11]) found that SNS addiction is related to higher level of narcissism and lower level of self-esteem. Several factors might contribute towards SNS addiction; dispositional factors (e.g., personality, self-esteem), socio-cultural factors (e.g., peers), and behavioral reinforcement factors (e.g., repetitive use of a medium) ( [6] [12]).…”
Section: Introductionmentioning
confidence: 99%